Producing natural functional and low-carbon milk by regulating the diet of the cattle—The fatty acid associated rumen fermentation, biohydrogenation, and microorganism response - Sun, Xiaoge; Wang, Yue; Ma, Xiaoyan; Li, Shengli; Wang, Wei (Frontiers in Nutrition, 2022)
In general, ruminant diets are low in fat content, hence fat supplementation can be provided to improve rumen activity, and the fatty acid (FA) profile of their meat and milk. However, polyunsaturated FA (PUFA), especially 18-carbon (C18) PUFA, the dominant fat sources for ruminants, have negative effects on microbial growth, especially on fibrolytic bacteria and protozoa. In turn, the rumen microbiota detoxifies C18 PUFA by a biohydrogenation (BH) process, transforming cis-C18 PUFA into trans-C18 PUFA and, finally, into saturated FA. Contrastingly, dietary C18 PUFA addition can modify the milk FA profile and ruminal mi-crobial ecosystem. In particular, it can improve the conjugated linoleic acid in milk which is considered as healthy for human beings, intensify the competition for metabolic hydrogen for propionate producing pathways and decrease methane formation. Therefore, lipid sup-plementation appears to be a promising dietary strategy to increase milk value and inhibit methane emission by ruminants. However, the effects of dietary fat supplementation on ru-men fermentation, feed digestion, and methane production vary among studies, which could be associated with type and amount of fat addition. Moreover, several bacterial species and strains have been considered to be affected by C18 PUFA or being involved in lipolysis, BH, or methane emissions. Therefore, this study aims to provide an overview of existing knowledge about the interactions between dietary fat (with a focus on C18 PUFA) and ru-men fermentation, BH reaction, milk fatty acid profile, methane production, and rumen microbiota.